2009
DOI: 10.1523/jneurosci.3587-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Multivoxel Pattern Analysis Reveals Increased Memory Targeting and Reduced Use of Retrieved Details during Single-Agenda Source Monitoring

Abstract: We used multivoxel pattern analysis (MVPA) of functional MRI (fMRI) data to gain insight into how subjects' retrieval agendas influence source memory judgments (was item X studied using source Y?). In Experiment 1, we used a single-agenda test where subjects judged whether items were studied with the targeted source or not. In Experiment 2, we used a multiagenda test where subjects judged whether items were studied using the targeted source, studied using a different source, or nonstudied. To evaluate the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
101
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 52 publications
5
101
0
Order By: Relevance
“…A few studies have reported a link between MVPA measures of cortical reinstatement and the subjective experience of recollection (Gordon, Rissman, Kiani, & Wagner, 2013;Ritchey, Wing, Labar, & Cabeza, 2013;Staresina, Henson, Kriegeskorte, & Alink, 2012;Kuhl, Rissman, Chun, & Wagner, 2011;Johnson et al, 2009;McDuff, Frankel, & Norman, 2009). However, most of these studies have assessed recollection as an all-or-none phenomenon that is either present or absent (e.g., with a remember/know paradigm; Tulving, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have reported a link between MVPA measures of cortical reinstatement and the subjective experience of recollection (Gordon, Rissman, Kiani, & Wagner, 2013;Ritchey, Wing, Labar, & Cabeza, 2013;Staresina, Henson, Kriegeskorte, & Alink, 2012;Kuhl, Rissman, Chun, & Wagner, 2011;Johnson et al, 2009;McDuff, Frankel, & Norman, 2009). However, most of these studies have assessed recollection as an all-or-none phenomenon that is either present or absent (e.g., with a remember/know paradigm; Tulving, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…MVPA relies on classifying neural activity during retrieval to dissociate broad manipulations such as category or task that are present during encoding (13)(14)(15)(16). MVPA, however, is unable to directly examine whether successful retrieval reinstates the neural representations of individual items.…”
mentioning
confidence: 99%
“…During the critical retrieval phase, subjects were presented with word cues and attempted to covertly recall target associates, indicating by button press whether they were able to recall the specific image vs. a more general memory for the category of the image (face/scene). The scanned encoding and retrieval rounds were followed by a behavioral posttest that reassessed memory for AB and DE pairs, allowing for measurement of the impact that AC learning had on memory for previously learned AB pairs.Reactivation was assessed via multivoxel pattern analysis (MVPA)-a technique well-suited to measuring reactivation (20)(21)(22). Accordingly, we first trained a pattern classifier to discriminate patterns of activity within the VOTC that were associated with the encoding of words paired with faces vs. scenes; we then applied the classifier to retrieval trials to estimate the degree to which VOTC responses reflected face vs. scene reactivation-that is, the fidelity with which target memories were retrieved.…”
mentioning
confidence: 99%
“…Reactivation was assessed via multivoxel pattern analysis (MVPA)-a technique well-suited to measuring reactivation (20)(21)(22). Accordingly, we first trained a pattern classifier to discriminate patterns of activity within the VOTC that were associated with the encoding of words paired with faces vs. scenes; we then applied the classifier to retrieval trials to estimate the degree to which VOTC responses reflected face vs. scene reactivation-that is, the fidelity with which target memories were retrieved.…”
mentioning
confidence: 99%